HRONIČNA RENALNA INSUFICIJENCIJA KOD PACIJENTA NA SUPSTITUCIONOJ TERAPIJI METADONOM - Knezevic, Snezana B.; Dugalić, Branimir D.; Dugalić, Anđelka S. (General Practice, 2021)
Introduction. Opioid addiction is a chronic condition related to different morbidities. The methadone substitution therapy of the opioid addict, combined with social, health, and psychological services is a gold standard of the treatment. All opioids display numerous side effects. Kidney damage in opioid addicts is due to sepsis, rhabdomyolysis, decreased glomerular filtration, hypotension, pulmonary edema, renal lipidosis, or amyloidosis.Case report. The male patient, 40, on methadone substitution therapy feels weak, sweats excessively. Lab work: potassium 9.87 mmol/L, BUN 18.3 mmol/L, creatinine 268 µmol/L, urea clearance 0,20 ml/s, creatinine clearance 0,81 ml/s, eGFR 23 ml/min/1,73m2, creatine phosphokinase 1180 IU/L, Hgb 79 g/L, Er 2.81x1012/L, C-reactive protein 13.2 µg/mL, Le 7.41x109/L, PCO2 41 mmHg, HCO3 22 mmol/L, and acidosis, pH 7.21. Blood pressure 130/80 mmHg and heart rate 64 bpm, ECG shows prolonged PR interval and high T waves. He was treated with crystalloid iv solutions, 8.4% bicarbonate solutions, diuretics, calcium gluconate, shortacting insulin, antibiotics, and anticoagulants. After therapy, there is an improvement in his potassium levels, diuresis, and ECG. After 24 days of hospital treatment, he was discharged to home care.Conclusion. Patients on methadone substitution therapy have a higher risk of multiple organ damage. Kidney function is especially at risk. It is of utmost importance to raise awareness among physicians of the danger of rabdomyolysis in these patients. Regular lab checks in patients on methadone substitution therapy can timely detect severe acute and chronic kidney complications and enable timely treatment.
Keywords: kidney damage; maintenance therapy; primary healthcare